Prayer has spoiled everything : possession, power, and identity in an Islamic town of Niger - Masquelier, Adeline Marie, 1960- (Body, commodity, text., 2001)
An ethnographic and historical account of bori spirit possession and its relation to Islam, colonialism, and the state.